Occupational, physical, sexual and mental health and violence among migrant and trafficked commercial fishers and seafarers from the Greater Mekong Subregion (GMS): systematic review - Pocock, Nicola S. (Glob Health Res Policy, 2018)
BACKGROUND: Little is known about the health of GMS commercial fishers and seafarers, many of whom are migrants and some trafficked. This systematic review summarizes evidence on occupational, physical, sexual and mental health and violence among GMS commercial fishers/seafarers. METHODS: We searched 5 electronic databases and purposively searched grey literature. Quantitative or qualitative studies reporting prevalence or risk of relevant outcomes were included. Two reviewers independently screened articles. Data were extracted on nationality and long/short-haul fishing where available. RESULTS: We identified 33 eligible papers from 27 studies. Trafficked fishers/seafarers were included in n=12/13 grey literature and n=1/20 peer-reviewed papers. Among peer-reviewed papers: 11 focused on HIV/AIDS/sexual health; nine on occupational/physical health; one study included mental health of trafficked fishers. Violence was quantitatively measured in eight papers with prevalence of: 11-26% in port convenience samples; 68-100% in post-trafficking service samples. Commercial fishers/seafarers whether trafficked or not worked extremely long hours; trafficked long-haul fishers had very limited access to care following injuries or illness. Lesser-known risks reported among fishers included penile oil injections and beriberi. We found just one work safety intervention study and inconclusive evidence for differences in the outcomes by nationality. Findings are limited by methodological weaknesses of primary studies. CONCLUSION: Results show an absence of high-quality epidemiological studies beyond sexual health. Formative and pilot intervention research on occupational, physical and mental health among GMS commercial fishers and seafarers is needed. Future studies should include questions about violence and exploitation. Ethical and reporting standards of grey literature should be improved. TRIAL REGISTRATION: Review registration number: PROSPERO 2014: CRD42014009656. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s41256-018-0083-x) contains supplementary material, which is available to authorized users.